Household Hygiene Idiorhythmias - Costanzo , Giorgia (E|C, 2024)
How does the sense of dirty and clean change as the sociality of the home changes? What kind of dirt do pets and children produce? What processes of discoursivisation are involved? How is it narrated and what value is invested in it? In the name of hygiene, we create strict household rules that try to bring order: the dog is not allowed in the bed, we mustn't enter the house with our shoes on, children are not allowed to eat on the floor, but they can lie on the sofa where the cat is not supposed to sleep. Hygiene is not just a contemporary obsession, but an ongoing superficial work that underlies deep values and mechanisms that regulate human and non-human relationships. Cleaning is one of the forms of expression that shape a social content: being together. The comparative analysis of the advertising of domestic cleaning products will allow us to examine how contemporary society organises cohabitation and sociality through the management of cleaning practices.